2002
DOI: 10.1038/sj.onc.1205190
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumour cell growth by hyperforin, a novel anticancer drug from St. John's wort that acts by induction of apoptosis

Abstract: Hyperforin is a plant derived antibiotic from St. John's wort. Here we describe a novel activity of hyperforin, namely its ability to inhibit the growth of tumour cells by induction of apoptosis. Hyperforin inhibited the growth of various human and rat tumour cell lines in vivo, with IC 50 values between 3 ± 15 mM. Treatment of tumour cells with hyperforin resulted in a dose-dependent generation of apoptotic oligonucleosomes, typical DNA-laddering and apoptosis-speci®c morphological changes. In MT-450 mammary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
155
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(170 citation statements)
references
References 44 publications
8
155
0
7
Order By: Relevance
“…Indeed, HF elicited PS externalization, Our results showing that DNA fragmentation and several effects of HF described here, including PARP cleavage, are inhibited by the general caspase inhibitor z-VAD-fmk and that caspase-3 activity is stimulated highlight the role of the caspase pathway in HF-mediated apoptosis of B-CLL cells. These results are in agreement with previous reports on other types of tumor cells, 13,14 except that only a slight caspase-8 activation was found here. HF is not known to bind to a receptor displaying a death domain and, with the exception of the D(1) dopamine receptor, it does not interact with biogenic amine receptors and transporters.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Indeed, HF elicited PS externalization, Our results showing that DNA fragmentation and several effects of HF described here, including PARP cleavage, are inhibited by the general caspase inhibitor z-VAD-fmk and that caspase-3 activity is stimulated highlight the role of the caspase pathway in HF-mediated apoptosis of B-CLL cells. These results are in agreement with previous reports on other types of tumor cells, 13,14 except that only a slight caspase-8 activation was found here. HF is not known to bind to a receptor displaying a death domain and, with the exception of the D(1) dopamine receptor, it does not interact with biogenic amine receptors and transporters.…”
Section: Discussionsupporting
confidence: 83%
“…11 Recently, it was reported that extracts of St John's wort containing HF induce growth inhibition and apoptosis of human and rat malignant cells in vitro as well as in vivo. 12,13 Similar effects, associated with activation of caspases, were also shown with the myeloid leukemia cell lines K562 and U937. 14 However, it is not known whether HF could exert activity in B-cell chronic lymphocytic leukemia (B-CLL), a malignancy which results from a defect of apoptosis rather than an impaired control of lymphoproliferation.…”
Section: Introductionmentioning
confidence: 49%
“…Inhibition of proliferation has been reported also in vivo (6), and the cytotoxic effect of Hyp on human malignant cells was correlated with the induction of caspase-driven apoptosis (7). This finding could be of great oncological relevance, but no study has yet validated Hyp as an anticancer lead by demonstration of its effectiveness against invasive and metastatic aggressiveness.…”
Section: Introductionmentioning
confidence: 87%
“…However, an even more pronounced protective effect should be registered in spontaneous metastasis models where more steps of the process can be hindered by Hyp, including cell proliferation and survival, as already proved (ref. 6 and here), as well as intravasation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation